Pengaruh Corporate Social Responsibility dan Iklan Islami terhadap Reputasi Perusahaan dengan Kepuasan Pelanggan Sebagai Variabel Interverning dalam Perspektif Bisnis Islam: (Studi Pada Pengguna Shopeefood Di Kota Bandar Lampung) - A. Zuliansyah; Nurhayati Nurhayati; Della Amelya (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the effect of Corporate Social Responsibility and Islamic Advertising on Corporate Reputation with Customer Satisfaction as an intervening variable on Shopeefood application users in Bandar Lampung City from an Islamic business perspective. This study uses a quantitative approach, data collection is carried out through a survey with a questionnaire in the form of a google form. The population in this study are Shopeefood application users and domiciled in Bandar Lampung City. The sample of this study was 100 respondents using a non-probability sampling method with a purposive sampling technique, and using SEM analysis tools using PLS and the results of data processing obtained using smartpls. The results showed that the variables of Corporate Social Responsibility and Islamic Advertising have a positive and significant effect on Corporate Reputation. Customer Satisfaction has a positive and significant effect on Corporate Reputation. The Customer Satisfaction variable mediates the influence of Corporate Social Responsibility on Corporate Reputation. Meanwhile, Customer Satisfaction is unable to mediate the influence of Islamic Advertising on Corporate Reputation.